ROLE OF SURGERY IN PATIENTS WITH ADVANCED CANCER BREAST WITH OR WITHOUT INITIAL CHEMO-HORMONO-RADIOTHERAPY - Gaikwad, Onkar; Gokul, Jorvekar (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Role of surgery has changed or changing globally in the form of down staging and surgery in locally advanced breast cancer to Modified Radical Mastectomy with axillary clearance in locally operable stage IV breast cancer with good performing status. Aim & Objective: To study the role of surgery in patients with advanced cancer breast with or without initial Chemo-Hormono-Radiotherapy. Material and methods: The study includes 100 cases of advanced breast cancer-stage IIIb and stage IV, undergoing surgery with or without initial Chemo-Hormono-Radiotherapy. Information regarding family history of similar complaints, operative detailed history, treatment received by the patients was recorded also recorded. Postoperatively patients were followed up every monthly for completion Chemotherapy and clinical examination for first 3 months than 3 monthly interval. Patients were thoroughly examined for local site or Axillary recurrence and progress of the disease in the form of supraclavicular lymph node, opposite breast, arm edema, bony tenderness, chest infection and liver enlargement. Result: The highest percentage of breast cancer is reported in age group 51-60 years of age. Mean age of presentation was 52 years. The minimum age of presentation was 30 years and maximum was 80 years. Our study reported infiltrating ductal carcinoma to be the most frequent of all carcinoma of breast, comprising 95% of cases.Â  7% of patients underwent Palliative Mastectomy while 73% of cases underwent Modified Radical Mastectomy with Axillary clearance. Axillary clearance (level III) was done in 80 patients. While Level I axillary clearance was done in 12 patients. 7 patients underwent palliative mastectomy. Only 58 patients received Neoadjuvent Chemotherapy. 75% of patients received Radiotherapy postoperatively. Conclusion: Even though there is definite role of surgery in breast cancer in the early stage of breast cancer, the incidence of patients presenting with advanced breast cancer in a rural population is alarming. The treatment of stage IIIb and stage IV breast cancer is multimodal, evolving and challenging which is further complicated by resistance or refusal of Neoadjuvent Chemotherapy or Radiotherapy by the rural population. Key words: Advanced cancer breast, Chemo-Hormono-Radiotherapy, Treatment modalities.